#### Answer

$8^{2}$ = $(6)^{2}$ + $(9)^{2}$ - 2*6*9*cos β

#### Work Step by Step

Given data
a=6,b =8, c=9
Using theorem 11.4.3
In triangle ABC
$b^{2}$ = $a^{2}$ + $c^{2}$ - 2ac cos β
$8^{2}$ = $(6)^{2}$ + $(9)^{2}$ - 2*6*9*cos β

Published by
Cengage

ISBN 10:
978-1-337-61408-5

ISBN 13:
978-1-33761-408-5

$8^{2}$ = $(6)^{2}$ + $(9)^{2}$ - 2*6*9*cos β

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.